2013
DOI: 10.1186/1824-7288-39-80
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on diagnosis and management of childhood asthma and food allergies

Abstract: The epidemic of childhood allergic disorders has been associated to the decline of infectious disease. However, exposure to many triggers (airborne viruses, tobacco smoke, pollution, indoor allergens, etc.) contribute to the disease. Breast feeding practices, nutrition, dietary and obesity also play a multifaceted role in shaping the observed worldwide trends of childhood allergies. Guidelines for treatment are available, but their implementation is suboptimal. Then developed countries are slowing learning int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 123 publications
0
12
0
4
Order By: Relevance
“…Corroborating our findings, other studies have demonstrated that, at the time of hospital admission, there is a predominance of children and adolescents with adequate nutritional status when assessed by anthropometric parameters. 3 , 21 , 22 , 23 On the other hand, weight loss is frequent during hospitalization, which reinforces the importance of early identification of children at risk of deteriorating nutritional status. A prospective study showed that 65% of the children had weight loss during hospitalization and the factors most predictive of its occurrence were: reduced food intake, pain and severity of the disease.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Corroborating our findings, other studies have demonstrated that, at the time of hospital admission, there is a predominance of children and adolescents with adequate nutritional status when assessed by anthropometric parameters. 3 , 21 , 22 , 23 On the other hand, weight loss is frequent during hospitalization, which reinforces the importance of early identification of children at risk of deteriorating nutritional status. A prospective study showed that 65% of the children had weight loss during hospitalization and the factors most predictive of its occurrence were: reduced food intake, pain and severity of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…22 A similar frequency was found in Dutch and Italian hospitals, with 62 and 68% of the patients presenting moderate or high nutritional risk, respectively. 3 , 8 When the nutritional profile is evaluated according to the type of hospital, a multicenter study carried out in the Netherlands noted a higher prevalence of high nutritional risk in university hospitals, when compared to other hospitals, of 15 and 5%, respectively. The researchers suggest that this is due to a higher number of patients being hospitalized with some chronic disease in university hospitals, in comparison to others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of childhood asthma is associated with a broad range of factors including genetics, environmental factors, and lifestyle [ 4 ]. Guidelines for treatment have been published, but their implementation has been reported to be less than optimal [ 5 ]. In addition, many of the commonly prescribed drug treatments for asthma have undesirable side effects [ 6 ], including effects on growth in children by inhaled corticosteroids [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…13,14,15 Susceptibility to allergy is often influenced by several factors such as age, gender, heredity which is by far the most significant, and environmental factors such as exposure second-hand smoke and to household pets. 16,17,18,19,20 Allergic disorders are characterized by high levels of IgE which in turn are found to be associated with allergy prevalence and severity. 21,22,23 About 70-90% of allergic patients worldwide are sensitized to HDMs.…”
Section: Discussionmentioning
confidence: 99%